Perfil do uso de antibióticos em um hospital da fronteira oeste do Rio Grande do Sul - Charão, Andressa Chaves Deobaldo (2022)
The indiscriminate use of antibiotics is pointed out as the main cause of microbial resistance. This phenomenon is seen as a global public health problem that compromises the effectiveness of treatments. Several factors that contribute to this context stand out, such as the empirical prescription of antibiotics. In this context, the objective of this study was to characterize the profile of antibiotic use by patients admitted to the clinical unit of a hospital on the western border of Rio Grande do Sul, during the period of 12 months (from September 2019 to August 2020). Data collection took place through the analysis of medical records available in the file, after discharge or death of patients from the hospital Clinical Unit. The sample consisted of 410 patient records. Of these, 55.52% were female and 49.02% were elderly, who remained hospitalized between 1 and 48 days, resulting in 89.4% hospital discharge and 11.3% deaths. The main causes of hospitalization were pneumonia (9.35%), urinary tract infections (7.94%) and nephritis (6.31%). The prescription of 36 different antibiotics was identified, of which 86% were administered intravenously and 12% orally. Among the most frequently prescribed, broad-spectrum drugs stood out, such as cephalothin sodium (189), followed by ceftriaxone (134) and ciprofloxacin (46), classified as “other beta-lactam antibacterials” (63.18%). and quinolones (11.43%). Of the total number of medical records evaluated, 95.6% contained empirical prescriptions for antibiotics, without performing the culture test and antibiogram. Therefore, there is a need to assess the financial impact of the current prescription practice in the institution under study, as well as the implementation and effective operation of a Hospital Infection Control Commission, with the structuring of policies for prescription and monitoring of use of antimicrobials.